Torrefaction of pelletized corn residues with wet flue gas. (August 2019) - Onsree, Thossaporn; Tippayawong, Nakorn; Williams, Travis; McCullough, Katie; Barrow, Elizabeth; Pogaku, Ravindra; Lauterbach, Jochen
Highlights: Wet flue gas can be employed for the torrefaction of corn residue pellets. Residence time and steam concentration affect product yields significantly. Steam accelerates decomposition of hemicellulose and lignin and increases porosity. Raman spectroscopy revealed graphene structures in torrefied pellets. Abstract: Corn residue pellets were torrefied with wet flue gas, simulated by steam (0–21% v/v), CO2 (12% v/v), and O2 (4% v/v), balanced with N2 as reactive gas, in a fixed bed reactor at 260 °C of temperature and at 10–40 min of residence time. The distribution and yields of torrefied pellets, liquid, and gas products were examined. The microstructural changes of torrefied pellets were evaluated by Raman spectroscopy and scanning electron microscopy, while the components of gas products were analyzed by mass spectrometry. Residence time and steam concentration in the reactive gas were found to have significant effects on the products yield distribution, the porosity of the torrefied pellets, and the concentrations of CO, CH4, H2, and CO2 in the gas products. At high steam concentrations, the decomposition reaction of hemicellulose and lignin in the raw pellets, and the formation of the graphene structures in torrefied pellets occurred faster.